A new RelB‐dependent CD117+CD172a+ murine DC subset preferentially induces Th2 differentiation and supports airway hyperresponses in vivo. Issue 6 (6th April 2018) - Andreas, Nico; Riemann, Marc; Castro, Carla N.; Groth, Marco; Koliesnik, Ievgen; Engelmann, Christian; Sparwasser, Tim; Kamradt, Thomas; Haenold, Ronny; Weih, Falk
Abstract: The NF‐κB transcription factor subunit RelB is important for the full activation of conventional dendritic cells (cDCs) during T‐cell‐dependent immune responses. Although the number of splenic DCs is greatly reduced in RelB null mice, the cause and consequences of this deficiency are currently unknown. To circumvent the impact of the pleiotropic defects in RelB null mice we used a reporter model for RelB expression (RelB Katushka mice) and conditionally deleted RelB in DCs (RelB CD11c‐Cre mice). Thereby, we can show here that RelB is essential for the differentiation of a CD117 + CD172a + cDC subpopulation that highly expresses RelB. Surprisingly, these DCs depend on p50 for their development and are negatively regulated by a constitutive p52 activation in absence of p100. The absence of p52/p100 had no influence on the homeostasis of CD117 + CD172a + cDCs. RelB‐dependent CD117 + CD172a + DCs strongly induce the production of the type 2 cytokines IL‐4 and IL‐13, as well as GM‐CSF from naïve Th cells. Consequently, mice lacking RelB in cDCs show an attenuated bronchial hyperresponsiveness with reduced eosinophil infiltration. Taken together, we have identified a new splenic RelB‐dependent CD117 + CD172a + cDC population that preferentially induces Th2 responses. Abstract : Conventional DCs (cDCs) are very potent in immune regulation. Via RelB/p50 complexes the NF‐κB pathway supports the differentiation of a CD117 + CD172a + cDC subpopulation in the spleen. This subset preferentially induces Th2 polarization and thereby essentially facilitates lung inflammation.